Penerapan Penyusunan Laporan Keuangan UMKM Berdasarkan (SAK EMKM) pada Usaha Toko Bangunan Aroma - Sinta Kistianti; H. Musthafa Kamil (Journal Economic Excellence Ibnu Sina, 2024)
This research was conducted at the Aroma Building Store, which is one of the MSMEs in West Jakarta City. This research aims to find out the application of preparing financial reports based on the Micro, Small and Medium Entity Financial Accounting System (SAK EMKM) at the Aroma Building Store and how to apply the financial reports. aware of SAK EMKM at the Aroma Building Store. The type of research used in the research is a qualitative descriptive approach. The results of this research show that the Aroma Building Shop business owner's understanding of SAK EMKM is still low, and recording and preparing financial reports is still simple based on the business owner's understanding. The owner does not carry out accounting records based on SAK ElMKM (Financial Accounting Standards for Small and Medium Enterprises) because the business owner does not understand, so the recording and preparation of financial reports is still carried out only and manually based on the understanding of the owner of the MSME business, which lacks knowledge and lack of manpower to make financial reports. The implementation of preparing financial reports based on SAK EMKM at the Aroma Building Store has had a positive impact on the company, where by implementing the preparation of financial reports based on the Micro, Small and Medium Entity Financial Accounting System (SAK EMKM) so that business owners understand and know that there are standards that serve as guidelines in carrying out recording financial reports for business development.